Exploring the Lexicon of Philippine Daily Inquirer Editorials (Journal of Natural Language and Linguistics, 2023)
This study aimed to explore the lexicon of the editorials in the Philippine daily inquirer as it only replicates the research done by Bautista on Philippine English. It aimed to come up with a list of new and old words found in the editorials that are published from January to April 2018. The study employed discourse analysis design to determine the Philippine English words from the Philippine Daily Inquirer editorials. The Advil- Macquarie Philippine English Dictionary published by De La Salle University was the basis of the data analysis. From the data that was analyzed, there are new and old words in the lexicon used by editorial writers in their editorial as it would be concluded that the editorial writers who are an acrolect use Philippine English in writing. From the new words that were discovered, it could be deduced that Philippine English, just like any language is also evolving as it adapts new words in its set of vocabularies. It is proven that there is really Philippine English in the country as was found out by the pioneering research of Llamzon (1969).